Magnesium-catalyzed primary, secondary, and tertiary amide hydroboration - Mahata, Biplab; Devaraj, V.; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2025)
Catalytic hydroboration of amides is highly important because the resultant amines are commonly found in natural products, pharmaceuticals, agrochemicals, dyes, and other applications. In comparison to the conventional reduction of amides using (over)stoichiometric reductants, hydroboration of amides using magnesium compounds represents a green and sustainable approach because magnesium is both Earth abundant and environmentally benign. However, there is only one report on magnesium-catalyzed deoxygenative hydroboration of secondary and tertiary amides. Here, we describe the synthesis and structural authentication of two new magnesium compounds (1 and 2) featuring a flexible PNP ligand and the utilization of 2 as a catalyst for the pinacolborane-mediated reduction of primary, secondary, and tertiary amides to amines. The reaction scope is explored, and a mechanism is proposed based on experimental and theoretical insights.